Human Resources Management Strategy to Attract Workes (A Study Case in Pekalongan Batik Cluster SMEs) - Ajiatmojo, Muhammad Akbar; Kartika, Lindawati (Jurnal Manajemen Teknologi, 2025)
Abstract. SMEs (Small and Medium Enterprises), including batik (traditional Indonesian technique for decorating fabric using wax-resist dyeing) SMEs, significantly contribute to GDP and employment in Indonesia. Pekalongan regency is one of the centers of batik production and development in Indonesia, which occurs through interconnected SMEs, commonly called clusters. Currently, batik cluster SMEs in Pekalongan do not have a competitive advantage in the market, characterized by declining sales, inability to meet consumer demand, errors in the production process, low technology absorption, and lack of innovation. One of the causes of this situation is the declining interest of workers in employment at batik SMEs. Therefore, there must be an effort to increase worker interest to create a competitive advantage for batik SMEs in Pekalongan. This study used the soft system methodology (SSM) approach with strategic entrepreneurship as the theoretical framework. The resource persons were 13 owners/managers of batik SMEs in Pekalongan, plus two experts from external SMEs. This research produced a conceptual model of human resources management strategies from stakeholders to increase workers' interest in batik SMEs in Pekalongan by intensifying batik artists regeneration efforts through revitalizing batik tourism in Pekalongan. Such efforts involve vocational schools for batik, intensifying batik content in the media, creating national/international batik events, formulating WSS (Wage Structure and Scale)  for workers, and improving and standardizing workers' competencies. Keywords: batik, competitive advantage, SME, soft system methodology, worker attraction.